Optical Binding Force between Two Chiral Spheres by an Incident On-axis Gaussian Beam. (2015) - Zhu, Yuanyuan; Wu, Zhensen; Li, Zhengjun; Shang, Qingchao
Abstract: According to the electromagnetic scattering of two spheres, the incident on-axis Gaussian beam is expanded in terms of spherical vector wave functions (SVWFs), and the beam shape coefficients are obtained by applying the localized approximation method. Using the addition theorem, the interaction scattering fields of two chiral spheres and the internal fields are also expanded in terms of SVWFs. Based on the continuous tangential boundary conditions, the scattered field coefficients are derived analytically. Utilizing the Maxwell's stress tensor integration technique, the optical binding force between two chiral spheres is formulated explicitly. Numerical simulations of the binding force are carried out. The effects of the beam width and the radius of the sphere on the force are analyzed. The numerical results are compared with the results from references.